Media Pembelajaran Mobuya Untuk Pembelajaran Keragaman Budaya - Syamsijulianto, Tri (Jurnal Penelitian dan Pengembangan Pendidikan, 2020)
The purpose of this research is to develop thematic learning media materials the beauty of cultural diversity through learning media development mine own country Mobuya in elementary school. Media development methods in this study is a ADDIE Model (analysis, design, development, implementation, and evaluation). Media developed consists of learning Mobuya media, material cultures in West Kalimantan, and the manual, as for the results of validation include validation of the material retrieved 92.50% with a very worthy category, validation of the syllabus obtained 92, 30% with a very worthy category, validation RPP gained 93, 33% by category is well worth the first learning media validation, retrieved 70, 83% by category are fit enough for the second validation obtained 74, 19% by category is pretty decent. The result of the question form teacher on learning Mobuya learning media on the 22nd of January 2019 obtained results of 88.75% question form the application of learning media use by category is very viable, next on 23 January 2019 results obtained from the implementation of learning by using learning media of 96, 25% by category is very worthy to be used on the learning process in schools thematic basis. Limited trials retrieved retrieved from sngket that results in a spread on the learning process gained 97, 53%. Field trials retrieved pretest results with an average of 54, 70 and post test obtained an average of 68, 4.